2019
DOI: 10.1002/adem.201900125
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Passivation Layer by Cr Diffusion of 301 Stainless Steel Facilitated by SMAT

Abstract: AISI 301 stainless steel (SS) is known for its high strength and hardness but tends to be less corrosion resistant for many applications. Several attempts have been made in the past to investigate its corrosion behavior by different methods. However, current knowledge is insufficient on its corrosion resistance when subjected to surface treatment. In this work, a new route to enhance the corrosion resistance of nanostructured 301 SS using surface mechanical attrition treatment (SMAT) method is described. SMAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The SMAT method, which is preferable to other methods such as coating/deposition [3] , [4] in retaining the inherent properties of materials after treatment, has been extensively described in the literature [5] , [6] with application in aircraft, oil and gas, etc. [7] , [8] , [9] , [10] . After SMAT, the treated surface was slightly polished to reduce the effect of oxidation and surface roughness on the corrosion behaviour.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The SMAT method, which is preferable to other methods such as coating/deposition [3] , [4] in retaining the inherent properties of materials after treatment, has been extensively described in the literature [5] , [6] with application in aircraft, oil and gas, etc. [7] , [8] , [9] , [10] . After SMAT, the treated surface was slightly polished to reduce the effect of oxidation and surface roughness on the corrosion behaviour.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The corrosion behaviour of nanostructured 316 stainless steel has been experimented with through polarization test in 0.6 M NaCl aqueous solution at room temperature [55,56]. From the nanostructured layers, the surface mechanical attrition treatment (SMAT) and corrosion behaviour data of stainless steel 316 is obtained.…”
Section: Surface Mechanical Attrition Treatment (Smat)mentioning
confidence: 99%
“…17-4 PH steel shown better corrosion resistance in 0.5 M H 2 SO 4 when solution heat treated at 1040 0 C and subsequent aging at temperature 480 0 C [77] . Olugbade et al [78][79][80][81] developed a new method of creating nano structured passive oxide film on surface of steels using surface mechanical attrition treatment (SMAT). They successfully applied this method on the surfaces of SS 316L, 301 and 17-4 PH and found that SMAT was effective in increasing corrosion resistance of these steels.…”
Section: Characteristics Of Stainless Steelsmentioning
confidence: 99%